Formulasi Ekstrak Etanol Kulit Kopi (Coffea arabica L.) dalam Sediaan Sabun Padat sebagai Pelembab Alami - Maimunah, Siti; Dari, Salmiah Wulan; Prayoga, Andre (Program Studi S1 Farmasi, STIKES Senior, Medan, 2025)
Coffee skin is rich in antioxidants, vitamins, and minerals that are beneficial for skin health and softness. This study aims to determine the ethanol extract of coffee skin (Coffea arabica L.) formulated in solid soap preparations and effective concentrations of ethanol extract of coffee skin (Coffea arabica L.) concentrations of 2.5% (F1), 5% (F2), and 7.5% (F3) as a natural skin moisturizer in solid soap preparations. This study used an experimental method. Wet sorting, drying, characteristics of simplicia, phytochemical screening, maceration with 70% ethanol, making coffee skin extract with a concentration formulation of 2.5%, 5%, and 7.5% as a blank is a solid soap preparation without the addition of coffee skin extract, examination of the coffee skin extract solid soap preparation, namely organoleptic test, soap pH measurement, homogeneity test, irritation test, and finally humidity test. The four solid soap formulas are homogeneous. pH 9.2-10.5. The results of increasing the humidity of solid soap preparations from 25 volunteers for 28 days from ethanol extract of coffee skin (C. arabica L.) with each concentration were F1 (24.87%), F2 (35.40%), F3 (61.61%), and blank (23.84%). Most preferred in F1. The results of the Post-Hoc Test Turkey HSD analysis after observation from week I to week IV showed a p value> 0.05 meaning there was no significant difference in each formulation in the humidity test. Coffee skin extract (C. arabica L.) can be formulated into solid soap preparations.